A consumer neuroscientific method for assessing usability: eye-tracking visual fatigue in visually complex M-commerce applications - Johnson, Alexandra (School of Management Studies, 2025)
Purpose: Mobile commerce (m-commerce) applications (apps) need to be studied in terms of their visual element richness, usability and how these impact the visual fatigue that is felt by users and their overall system usage. The purpose of this paper is to present and discuss a conceptual model that seeks to establish a method for measuring visual fatigue using eye-tracking and examine its relationship with usability across varying levels of visual complexity in m-commerce apps. It aims to develop and extend existing research on the design of m-commerce apps in terms of the amount of visual elements to needed to satisfy users while mitigating the effect of visual fatigue and usability issues. Study Design/Methodology/Approach: The study utilised a mixed-methods approach to gather data through utilising consumer neuroscience techniques, specifically eye tracking technology to develop an understanding between usability, visual fatigue and visual complexity when the users engage and experience a m-commerce app. This research explored 96 consumer reactions and responses to different visually complex m-commerce apps. Mixed methods is needed to compliment both qualitative and quantitative results and gather a deeper understanding of the complex data. Findings: A model measuring visual fatigue through eye-tracking technology is established to better understand the impact on users within the 18-35 South African cohort when exposed to different visually complex applications. Relationships between the dimensions of visual fatigue, usability, visual complexity, phone usage and context of use are explored through hypothesis testing. Research limitations/ implications: The first contribution of this study is the addition of research on how users from South Africa experience m-commerce applications. The second contribution stems from the model established to measure visual fatigue through eye-tracking techniques to better understand users and how they navigate and experience an application. Third we established the impact of visually complex, visually simple and visually moderate designs on users satisfaction and wellbeing. Finally the study revealed important elements to users of a m-commerce application through the mixed-methods approach. Originality/Value: The findings of this study have numerous implications for both marketing managers, app developers and user experience experts. The findings supply valuable insight into how multiple visual elements impact a user's experience and satisfaction when navigating a m-commerce application. The study found that a more visually complex system did not hinder a user's experience but instead encouraged positive feedback from users.